Electrocardiographic changes in patients undergoing targeted temperature management. Issue 4 (30th May 2020) - Jandu, Simi; Sefa, Nana; Sawyer, Kelly N.; Swor, Robert
Abstract: Objectives: Targeted temperature management is the recommended therapy for comatose patients after an out‐of‐hospital cardiac arrest resuscitation due to the reduction in neurological damage and improved outcomes. However, there may result in electrocardiographic instability depending on the degree of targeted temperature management, including minor or life‐threatening dysrhythmias or conduction delays. This project aims to describe the frequency of ECG interval changes and clinically relevant dysrhythmias in targeted temperature management patients. Methods: This is a retrospective observational study from January 2009 to December 2015. Patients who qualified for the study had a non‐traumatic cardiac arrest with a return of spontaneous circulation, received targeted temperature management at 33.5°C for 24 hours followed by 16 hours of rewarming. ECG interval changes and dysrhythmias were recorded immediately after return of spontaneous circulation, and at 24 and 48 hours post return of spontaneous circulation. Results: A total of 322 patients (age 61.0 ± 16.9 years) had targeted temperature management initiated during the study period, of which 169 had complete data and 13 died prior to completing 24 hours of hypothermia. There were statistically significant changes during targeted temperature management in heart rate (96.7 ± 26.0/min before targeted temperature management; 69.5 ± 19.1/min during, P < 0.001), QRS duration (115.1 ± 32.6 ms before targeted temperature management; 107.8 ± 27.9 ms during targeted temperature management, P < 0.001), and QTc (486.3 ± 52.8 ms before targeted temperature management; 526.9 ± 61.7 ms during targeted temperature management, P < 0.001). There were cardiac dysrhythmias that received treatment during cooling and rewarming. Conclusion: During the period of targeted temperature management and rewarming, we observed few self‐limiting ECG interval changes and no clinically significant dysrhythmias in this population during the period of targeted temperature management.